Molybdenum Oxide Supported on Ti 3 AlC 2 is an Active Reverse Water-Gas Shift Catalyst - Ronda-Lloret, Maria; Yang, Liuqingqing; Hammerton, Michelle; Marakatti, Vijaykumar S; Tromp, Moniek; Sofer, Zdeněk; Sepúlveda-Escribano, Antonio; Ramos-Fernandez, Enrique V; Delgado, Juan Jose; Rothenberg, Gadi; Ramirez Reina, Tomas; Shiju, N Raveendran (ACS sustainable chemistry & engineering, 2021)
MAX phases are layered ternary carbides or nitrides that are attractive for catalysis applications due to their unusual set of properties. They show high thermal stability like ceramics, but they are also tough, ductile, and good conductors of heat and electricity like metals. Here, we study the potential of the Ti AlC MAX phase as a support for molybdenum oxide for the reverse water-gas shift (RWGS) reaction, comparing this new catalyst to more traditional materials. The catalyst showed higher turnover frequency values than MoO /TiO and MoO /Al O catalysts, due to the outstanding electronic properties of the Ti AlC support. We observed a charge transfer effect from the electronically rich Ti AlC MAX phase to the catalyst surface, which in turn enhances the reducibility of MoO species during reaction. The redox properties of the MoO /Ti AlC catalyst improve its RWGS intrinsic activity compared to TiO - and Al O -based catalysts.